Cerebral infarction after fractionated stereotactic radiation therapy of benign anterior skull base tumors. (February 2019) - Astradsson, Arnar; Munck af Rosenschöld, Per; Poulsgaard, Lars; Ohlhues, Lars; Engelholm, Svend Aage; Feldt-Rasmussen, Ulla; Marsh, Reginald; Roed, Henrik; Juhler, Marianne
Highlights: Cerebral infarction is common after FSRT of benign anterior skull base tumors. Cerebral infarction is not more common after FSRT than in the general population. Special attention should be paid to cerebral vasculature, during dose planning. Abstract: Background: The purpose of this study was to examine the occurrence of cerebral infarction (ischemic stroke), in a large combined cohort of patients with anterior skull base meningiomas, pituitary adenomas and craniopharyngiomas, after fractionated stereotactic radiation therapy (FSRT). Material and Methods: All patients, 18 years and older, with anterior skull base meningiomas, pituitary adenomas and craniopharyngiomas, treated with fractionated stereotactic radiation, in our center, from January 1999 to December 2015 were identified. In total 169 patients were included. The prescription dose to the tumor was 54 Gy for 164 patients (97%) and 46.0–52.2 Gy for 5 patients (3%). Cases of cerebral infarctions subsequent to FSRT were identified from the Danish National Patient Registry and verified with review of case notes. The rate of cerebral infarction after FSRT was compared to the rate in the general population with a one sample t -test after standardization for age and year. We explored if age, sex, disease type, radiation dose and dose per fraction was associated with increased risk of cerebral infarction using univariate Cox models. Results: At a median follow-up of 9.3 years (range 0.1–16.5), 7 of the 169 patients (4.1%) developed a cerebral infarction, at a median 5.7 years (range 1.2–11.5) after FSRT. The mean cerebral infarction rate for the general population was 0.0035 and 0.0048 for the FSRT cohort (p = 0.423). Univariate cox models analysis showed that increasing age correlated significantly with the cerebral infarction risk, with a hazard ratio of 1.090 (p = 0.013). Conclusion: Increased risk of cerebral infarction after FSRT of anterior skull base tumors was associated with age, similar to the general population. Our study revealed that FSRT did not introduce an excess risk of cerebral infarction.